2016
DOI: 10.1371/journal.pone.0155625
|View full text |Cite|
|
Sign up to set email alerts
|

Fibrous Hydrogels for Cell Encapsulation: A Modular and Supramolecular Approach

Abstract: Artificial 3-dimensional (3D) cell culture systems, which mimic the extracellular matrix (ECM), hold great potential as models to study cellular processes under controlled conditions. The natural ECM is a 3D structure composed of a fibrous hydrogel that provides both mechanical and biochemical cues to instruct cell behavior. Here we present an ECM-mimicking genetically engineered protein-based hydrogel as a 3D cell culture system that combines several key features: (1) Mild and straightforward encapsulation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…However, hydrogels have to be maintained in a hydrated state, therefore could possibly suffer from long term stability issues in vitro [112]. Also, densely crosslinked gels can inhibit the natural migration of cells [113].…”
Section: Hydrogel Scaffoldsmentioning
confidence: 99%
“…However, hydrogels have to be maintained in a hydrated state, therefore could possibly suffer from long term stability issues in vitro [112]. Also, densely crosslinked gels can inhibit the natural migration of cells [113].…”
Section: Hydrogel Scaffoldsmentioning
confidence: 99%
“…Encapsulated cells can change their encircled hydrogel matrix through the production of the new ECM. On the other hand, cell behavior can be affected by their surrounding hydrogel . Previous studies have demonstrated the positive effect of an RGD motif on cell behavior; specifically, it has been shown that arginine–glycine–aspartic acid (RGD) motifs of fibrin facilitate its binding to cells and growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cell behavior can be affected by their surrounding hydrogel. 41,42 Previous studies have demonstrated the positive effect of an RGD motif on cell behavior; specifically, it has been shown that arginine-glycine-aspartic acid (RGD) motifs of fibrin facilitate its binding to cells and growth factors. Cells bind to this motif by their integrins, which is a transmembrane glycoprotein connected to cell cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…In the tested scaffold, the pore size was in the range of that of natural extracellular matrix (ECM), which is much smaller than the average cell diameter. Additionally, the gels did not contain any degradation sites, which would allow the cells to remodel the material and migrate …”
Section: Silk Inspired Biomaterialsmentioning
confidence: 99%
“…Picture size: 370 × 370 µm 2 . Reproduced with permission . Copyright 2016, Public Library of Science.…”
Section: Silk Inspired Biomaterialsmentioning
confidence: 99%